Insulin-like growth factor family and its impact on pulmonary arterial hypertension: a review - Li, Nuo; Mo, Degang; Dai, Hongyan (Frontiers in Physiology, 2025)
Pulmonary arterial hypertension (PAH) is a progressive and life-threatening cardiopulmonary disorder with rising global prevalence and limited curative options. Although current therapies have improved clinical outcomes, they primarily offer symptomatic relief, underscoring the need for novel disease-modifying strategies. PAH pathogenesis involves multiple interrelated mechanisms, including genetic predisposition, endothelial dysfunction, inflammation, oxidative stress, and vascular remodeling. Among these, endothelial dysfunction and vascular remodeling are central to both disease initiation and progression. Endothelial dysfunction is an early and central event, leading to an imbalance between vasodilators and vasoconstrictors, increased vascular permeability, and a pro-thrombotic state. These changes initiate a cascade of vascular remodeling, characterized by pulmonary artery smooth muscle cell proliferation, fibroblast activation, and extracellular matrix deposition, ultimately resulting in increased vascular resistance and right ventricular failure. Recent evidence indicates that the insulin-like growth factor (IGF) family significantly contributes to both vascular remodeling and endothelial dysfunction in PAH. Through complex signaling networks involving IGF receptors and regulatory proteins, IGFs promote smooth muscle cell proliferation, extracellular matrix accumulation, and endothelial cell dysfunction—aggravating vascular alterations characteristic of the disease. While the IGF family—including IGFs, IGFBPs, and IGFBPLs—has been implicated in a range of cardiovascular disorders, its specific involvement in PAH remains insufficiently characterized. This review consolidates current evidence on the IGF family’s roles in PAH pathogenesis, with emphasis on its contributions to vascular remodeling, endothelial dysfunction, and right ventricular adaptation. By delineating the distinct yet interconnected actions of IGF-related molecules, this review aims to identify potential diagnostic biomarkers and therapeutic targets, ultimately advancing precision strategies for PAH management.